PERANCANGAN SISTEM INFORMASI E-BOOK KUNJUNGAN KERJA DI VICTORIA BUSANA BERBASIS WEBSITE MENGGUNAKAN METODE WATERFALL - Alhabasi, Muh Tantowi; Haryono, Wasis (Journal Information & Computer, 2023)
The design of the Work Visit E-Book Information System is the design of an application to obtain data on employees of central agency staff who visit branch agencies. Currently, there are still many agencies that still use conventional processes to record data in work visit books. At the same time, in today's digital age, Information technology plays an important role for every company to facilitate work. Victoria Busana Store is a company that is under the auspices of Ria Busana Group managed by PT. Ria Indah Mandiri, Victoria Busana Ciledug first time open on April 03, 2021, this store has 4 floors plus a basement led by 1 Coordinator Store Manager and 2 Supervisors, and has good internet facilities for its employees. Data entry activities for work visits by central staff in Victoria Busana Store still using the work visit book and recorded manually. The weakness of this manual system is that it takes a lot of time to find information and make reports in the administration section, which slows down the work process and lacks time efficiency. Therefore, with this application, it does not require a storage space for work visit book archives and also no budget is needed for the procurement of work visit books. Therefore, through the Job Training program, as a form of higher education tri dharma, Pamulang University provides a Working Visit E-Book Information System Application to Victoria Busana Ciledug Store to apply there. So it is very helpful for store administration staff and also makes it easier to fill in work visit data for staff who visit the store, simply by opening a browser and being flexible.